Wind power station. - Salit, Mohd Sapuan; Ismail, Napsiah; Usubamatov, Ryspek; Megat Ahmad, Megat Mohamad Hamdan (2009)
With fossil fuels steadily diminishing at an alarming rate due to uncontrolled exploitation by the industries around the globe, many industries are leading the way looking for alteernative energy sources. There are some abundantly available free alternative energy sources that mother nature hass blessed us with like solar energy, wind energy and the wave energy to name a few. The present invention generally relates to a power station, especially to a power station that utilized wind energyto generates its power. Unlike conventional wind machine which uses fixed angle blade, the present invention uses movable vanes that can open and close, alternately. In operation, the vane facing the wind will be in full capacity, while the vane going against the wind will be parallel to the wind; thereby minimizing resistant, and this has proven to improve efficiency tremendously.